Role of phosphorylation of Cdc20 in the regulation of the action of APC/C in mitosis - Shevah-Sitry, Danielle; Miniowitz-Shemtov, Shirly; Teichner, Adar; Kaisari, Sharon; Hershko, Avram (Proceedings of the National Academy of Sciences - PNAS, 2022)
The ubiquitin ligase APC/C (anaphase-promoting complex/cyclosome) is essential for the control of mitosis, and its activity is subject to tight regulation. In early mitosis, APC/C is inhibited by the mitotic checkpoint system, but subsequently it regains activity and promotes metaphase-anaphase transition by targeting cyclin B and securin for degradation. The phosphorylation of APC/C by the mitotic protein kinase Cdk1-cyclin B facilitates its interaction with its coactivator Cdc20, while the phosphorylation of Cdc20 inhibits its binding to APC/C. This raises the question of how Cdc20 binds to APC/C under conditions of high Cdk1 activity. It seemed possible that the opposing action of protein phosphatases produces a fraction of unphosphorylated Cdc20 that binds to APC/C. We found, however, that while inhibitors of protein phosphatases PP2A and PP1 increased the overall phosphorylation of Cdc20 in anaphase extracts from Xenopus eggs, they did not decrease the levels of Cdc20 bound to APC/C. Searching for alternative mechanisms, we found that following the binding of Cdc20 to APC/C, it became significantly protected against phosphorylation by Cdk1. Protection was mainly at threonine sites at the N-terminal region of Cdc20, known to affect its interaction with APC/C. A model is proposed according to which a pool of unphosphorylated Cdc20, originating from initial stages of mitosis or from phosphatase action, combines with phosphorylated APC/C and thus becomes stabilized against further phosphorylation, possibly by steric hindrance of Cdk1 action. This pool of APCCdc20 appears to be required for the regulation of APC/C activity at different stages of mitosis.